1995
DOI: 10.1515/znc-1995-1-217
|View full text |Cite
|
Sign up to set email alerts
|

Polyols that Accumulate in Renal Tissue Uncouple the Plasma Membrane Calcium Pump and Counteract the Inhibition by Urea and Guanidine Hydrochloride

Abstract: Sorbitol and mannitol, two stereoisomeric osmolytes, inhibit the ATP-dependent Ca2+ transport in inside-out vesicles derived from basolateral membranes from kidney proximal tubules. This inhibition (I0,5 = 400 and 390 mᴍ respectively) cannot be attributed to an in­ crease in Ca2+ permeability, since the rate of EGTA-stimulated Ca2+ efflux from preloaded vesicles is not modified by these osmolytes. In the presence of 1 ᴍ sorbitol or mannitol, Ca2+ uptake is inhibited by 70 and 75%, respectively. Since the Ca2+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that some osmolytes protect against the effects of urea and guanidinium chloride on the function of different enzymes [13,14,37–40]. We have previously shown that the inactivation of plasma membrane H + ‐ATPase by guanidinium chloride is not protected by trehalose [14]; however, when the solubilized enzyme was reconstituted in artificial liposome, the functional stability was increased, although the presence of trehalose did not contribute to further increase it [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that some osmolytes protect against the effects of urea and guanidinium chloride on the function of different enzymes [13,14,37–40]. We have previously shown that the inactivation of plasma membrane H + ‐ATPase by guanidinium chloride is not protected by trehalose [14]; however, when the solubilized enzyme was reconstituted in artificial liposome, the functional stability was increased, although the presence of trehalose did not contribute to further increase it [14].…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates and polyols can modulate the catalytic cycle of ion‐transporting ATPases, the so‐called P‐ATPases. These effectors decrease the K m for P i in the phosphorylation reaction catalyzed by the (Ca 2+ + Mg 2+ )ATPase from sarcoplasmic reticulum [52], uncouple Ca 2+ transport from ATP hydrolysis [13,53] and increase the rate of ATP–P i exchange catalyzed by the (Ca 2+ + Mg 2+ )ATPase from renal plasma membrane [37,38]. All these reactions are stimulated by a decrease in water activity and in protein solvation and are favored by the stabilization of E 2 conformation of these enzymes [52,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that many osmolytes, including carbohydrates and polyols, modulate the functions of different enzymes (Vieyra et al, 1989Chini et al, 1991;, 1995a, and, in addition, can preserve the function and/or structure of enzymes against chemical and physical stresses Meyer-Fernandes, 1994, 1996). It has been shown that among the carbohydrates tested, trehalose is the most effective, protecting yeast cytosolic enzymes against thermal inactivation ), suggesting why yeasts accumulate trehalose but not other carbohydrates when submitted to a heat shock (Wiemken, 1990;De Virgilio et al, 1991Hottiger et al, 1994;Meyer-Fernandes, 1994, 1996).…”
mentioning
confidence: 99%
“…Often, they are further classified as 'compatible' or 'counteracting' on the basis of their ability to affect the functional activity of proteins. Compatible osmolytes increase protein stability against denaturation with little or no effect on their function [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], whereas counteracting osmolytes have, in addition, the ability to offset the deleterious effects of denaturants on the catalytic activity [1,3,[6][7][8][11][12][13][17][18][19][20][21][22][23][24][25]. The counteracting solute effect can be viewed as a situation in which the tendency of a denaturant to unfold the protein structure is counterbalanced by a tendency of the solute to minimize the protein surface area in contact with water [18][19][20]25].Myosin (EC 3.6.4.1) belongs to the restricted family of motor proteins that transform the chemical energy of ATP into mechanical work.…”
mentioning
confidence: 99%